Impact of physical activity-based workplace wellness programs on improving worker productivity and health - Angeles Castro, Ruth E. (2024)
Inappropriate lifestyles are present in work environments that are significant challenges to the health and wellbeing of workers, especially in office environments. The review aims to comprehensively identify and analyze the effect of WPPAs (physical activity-based workplace wellness programs) on employee productivity and health and to provide information to organizations on the importance, benefits, and possible implementation strategies. A total of 321 original open access articles were identified from the SCOPUS database and 25 publications met the inclusion criteria. The (PICOC) strategy was used to define the eligibility criteria. The findings showed positive effects of physical activity on cardiovascular health, muscle strength, and work productivity. Each type of physical exercise could not be analyzed in depth because of their differences in terms of methodologies or population and since the research did not seek to evaluate the characteristics of these exercises, economic comparison of the investment was not performed as few sources offered such information. Although WPPAs hold promise for improving health and productivity at work, greater standardization is required in identifying the characteristics of physical activity, monitoring and understanding its long-term impacts to maximize its effectiveness and sustainability.